PENGKAJIAN DAMPAK REGULASI RUU EKSTRADISI TERHADAP EKONOMI MASYARAKAT INDONESIA: PENGKAJIAN DAMPAK REGULASI RUU EKSTRADISI TERHADAP EKONOMI MASYARAKAT INDONESIA - Alvon Christiano (Faculty of Law, Maranatha Christian University, 2020)
The law No. 1 of 1979 on extradition has been the legal basis for extradition in Indonesia. This law has some issues that should be corrected. Some of these issues consist of: (i) no arrangement regarding the deadline required to complete an extradition process, (ii) the extradition process in Indonesia has failed to reflect the government's desire to optimise Law enforcement activities. To note, optimal law enforcement activities will provide a state of political stability, prevent economic decline and or unstable circumstances, and the main objective is to maximize social welfare.